Understanding Managerial Work Values in Turkey - AŞKUN, OLCAY BİGE (SPRINGER, 2010)
The objective of this study was to explore certain managerial work values in Turkey. A total of 1023 managers from six Turkey regions participated in the study and filled out the questionnaires. Findings were analyzed using regression and anova analyses. A total of three managerial work value factors emerged, which was supported by the current value literature. It was found that there was a relationship between work values and organizational size. The lower the organizational size, the higher the proper values are held. However, organizational tenure, the number of subordinates a manager is responsible, and the educational level of a manager had no significant effect on holding work values. The proper values outnumbered the improper values significantly. The three most held work values were integrity, doing work with care and discipline, and achievement. The three least held values were cliquishness, laziness, and hypocrisy.
Keywords: values; managerial values; organization; Turkey; cultural values; proper values; improper values; STRUCTURAL-ANALYSIS; CULTURE; ORIENTATIONS; COUNTRIES; TURKISH; BRITISH; FACETS